Analyzing gait parameters in trail runners using wireless trunk accelerometry during real-world and treadmill incline running - Bergh, Oloff Charles Wessel (Stellenbosch : Stellenbosch University, 2020)
Thesis (M Sport Sc)--Stellenbosch University, 2020.